The Audit of Household Financial Management and Information Technology on Lifestyle in the New Normal Era - Putri, Rizqy Fadhlina; Putri, Rini Fadhillah (Accounting and Business Journal, 2022)
The purpose of this research is to formulate a study of the importance of auditing in the household, changes in information technology governance and the design of audit relationships and information technology on the quality of the family economy. The research method is Research and Development (R&D), with the samples used are Employees/Lecturers of UMN Al Washliyah Medan city and Deli Serdang Regency with the criteria of men and women who are married as many as 35 people, the data collection technique used is a scale questionnaire. Likert and secondary data. The result of this study is that household financial management using information technology is considered to be quite good, because some of them have recorded all household expenses and the lifestyle they apply is still varied, some have a high life style (high profile) and some are simple. (low profile).